2014
DOI: 10.1002/chem.201304724
|View full text |Cite
|
Sign up to set email alerts
|

Vortex‐Pattern Self‐Assembly in Mn‐Doped ZnSe Nanorods

Abstract: Spontaneous patterning of anisotropic nanostructures into ordered assemblies remains a challenging quest, which requires controlled innovative approaches. One way to achieve such ordering of 1D nanorods is by manipulating the varieties of interactions (attractive and repulsive forces) present in colloidal solutions of anisotropic nanocrystals. The other ingenuous pathway is solvent-evaporation-mediated self-organization of the 1D nanorods. By following the second protocol, we have achieved exclusive pillar sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Figure 1d presents a vortex type of such an assembly having a center where the assembly nucleated. 31 More TEM images of the self-assembly are provided in Figures S2−S4 in the Supporting Information. Rotation of the grid confirmed the vortex-type assembly as the center moved from one place to another with the grid rotation (Figure S5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1d presents a vortex type of such an assembly having a center where the assembly nucleated. 31 More TEM images of the self-assembly are provided in Figures S2−S4 in the Supporting Information. Rotation of the grid confirmed the vortex-type assembly as the center moved from one place to another with the grid rotation (Figure S5).…”
mentioning
confidence: 99%
“…The 2D assembly in Figure a covered more than 1 μm 2 area, and from the images in Figure b,c, these nanostructures were observed as nanorod self-assemblies. Figure d presents a vortex type of such an assembly having a center where the assembly nucleated . More TEM images of the self-assembly are provided in Figures S2–S4 in the Supporting Information.…”
mentioning
confidence: 99%
“…19−21 In fluid dynamics, a vortex is a region within a fluid where the flow mostly spins around an imaginary axis, either straight or curved. 22,23 Vortex and stirring-induced chirality has been established and reported for several organic achiral molecular and supramolecular systems such as ionic oligomers, 24 polymers, 25 proteins, 26,27 liquid crystals, 28,29 and for selfassemblies of supramolecular aggregates. 23,29−39 The vortexinduced chirality effect has mainly been observed and reported for self-assembled structures such as J-aggregate systems.…”
Section: Introductionmentioning
confidence: 99%
“…49 Using directional solvent evaporation from Mn-doped ZnSe nanorods, vortex patterning of semiconducting nanorods was realised. 22 It has also been demonstrated that rotating vortex flows can be used to achieve chiral separation at the micro-and nanoscales. 20,50 Here, we report the macroscopic optical activity effects in suspensions of plasmonic silver nanowires (Ag NWs) induced by vortex stirring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation